Studying the Materialization of Power in the Body: The Aesthetics of Neo-Spirituality - Aschenbrenner, Lina (Implicit religion, 2023)
The body plays a crucial role in a critical study of religion that is interested in the interrelation of religion and social and cultural power dynamics, yet the "body" often remains a floating signifier. This paper seeks to overcome this default mode of critical social and cultural studies by placing the focus on the material body. Through an examination of the aesthetics of the neo-spiritual Israeli movement practice known as Gaga, I demonstrate how power materializes in bodies during practice; how the bodily and material power dimensions, both implicit and non-linguistic, can by critically addressed; and how neo-spiritualities as part of a contemporary religious landscape evolve around the body as a medium of power dynamics. I exemplify my approach by examining two aesthetic processes in the context of Gaga: (1) the connection between the teacher of movement instruction and the Gaga class participant and (2) Gaga's body techniques that train sensory attention.